2017
DOI: 10.1371/journal.pone.0179035
|View full text |Cite
|
Sign up to set email alerts
|

Occult hepatitis B virus infection in HIV positive patients at a tertiary healthcare unit in eastern India

Abstract: Occult HBV infection (OBI), defined by the presence of HBV DNA in absence of hepatitis B surface antigen (HBsAg), is a significant concern in the HIV-infected population. Of 441 HIV+/HBsAg- patients analyzed, the overall prevalence of OBI was 6.3% (28/441). OBI was identified in 21 anti-HBc positives (17.8%), as well as among those who lacked any HBV-specific serological markers (2.2%). Comparison with HIV/HBV co-infection revealed that the levels of CD4, ALT, and HBV DNA were significantly lower during occult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 63 publications
(83 reference statements)
2
23
0
Order By: Relevance
“…In the present study, three novel OBI-unique mutations were detected in this ORF (xS11A, xV15I, and xP11S). Other studies in India reported OBI-associated mutations in the X ORF [ 113 ]. Some studies have reported deletions in the X region, which are linked to OBI.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, three novel OBI-unique mutations were detected in this ORF (xS11A, xV15I, and xP11S). Other studies in India reported OBI-associated mutations in the X ORF [ 113 ]. Some studies have reported deletions in the X region, which are linked to OBI.…”
Section: Discussionmentioning
confidence: 99%
“…In persons living with HIV (PLHIV), the prevalence of IAHBc ranges from 7% to 40% [4,16,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] and seems associated with the defect in T-cell response. This prevalence was found to be higher in cases of intravenous drug use or alcohol abuse [30], with older age, low CD4 T-cell count (below 200 cells per µL) and detectable HIV RNA [45].…”
Section: Definitions Of Isolated Anti-hbc Pattern and Occult Hepatitimentioning
confidence: 99%
“…(17,16) Anti-HBc was the sole HBV marker in 35 (17.77%) HIV patients, which is close to 17.50% (71 out of 405) and the 16% (38 out of 240) reported in Italy and Boston, respectively. (18,19) Isolated anti-HBc was detected in 12.7% in the study carried out by Aly (15) However, this percent is lower than what has been described in previous studies of HIV-positive patients, namely; the 26.80% detected in India, (20) and the 28.30% in Taiwan. (21) This high percent of sole anti-HBc in these countries may be explained by their high endemicity of HBV with subsequent higher prevalence of chronic and past HBV infection.…”
Section: Discussionmentioning
confidence: 64%
“…A percent approaching the present one has been recorded recently by Saha et al, among HIV positive patients in India. (20) They found OBI in 17.8% of patients with isolated anti-HBc. A higher percent of 24.5% was previously reported also from India (intermediate HBV endemicity) by Gupta and Singh in 2010.…”
Section: Discussionmentioning
confidence: 97%